ANALISIS PENGARUH DIMENSI BUDAYA TERHADAP NIAT MELAKUKAN WHISTLEBLOWING : PERBANDINGAN ANTARA MAHASISWA DAN ENGINEER - Dessy Finandari; Titis Wijayanto (Universitas Gadjah Mada, 2016)
This study aims to investigate the differences between engineering students and engineers on whistleblowing intentions, the effect of cultural dimensions on whistleblowing intentions, and the effect of ethnic differences on whistleblowing intentions. Each respondent was faced with three cases: a case involving a superior, a case involving a colleague, and an unknown case who was responsible. Each respondent is asked to provide an assessment related to the seriousness of cases, responsibilities and intentions to conduct whistleblowing internally or externally. Result indicate that students have intention to do internal whistleblowing higher than engineer. The lower the power distance, the higher the internal whistleblowing intention. The higher collectivism and long-term orientation, the higher the internal whistleblowing intention. Significant ethnic differences in intent to conduct whistleblowing are found in internal whistleblowing for unknown cases, and external whistleblowing in cases involving superiors